2017
DOI: 10.5539/ijc.v9n4p31
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Arthrocen, an Avocado/Soy Unsaponifiables Agent, on Inflammation and Global Gene Expression in Human Monocytes

Abstract: Osteoarthritis (OA) is the most common form of arthritis. Symptomatically characterized by stiffness and pain, OA is a chronic degenerative disease of joints. Of note, there is growing interest in the potential use of plant-based compounds for symptomatic treatment of OA. Arthrocen is a plant-derived agent consisting of a one to two ratio of avocado and soy unsaponifiable extracts. In order to decipher the potential mechanisms of Arthrocen’s action at the molecular level, we employed an in vitro assay using cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Avocado extract stimulates stroma-related enzymes, while soybean extract alone sensitively stimulates lysosomal enzymes with an acidic pH and, to a lesser extent, some neutral lysosomal proteases [11]. Consequently, the association of both extracts which constitute ASU exerts more powerful synergistic effects, different from that exercised by each of the individual components [12]. The action of both unsaponifiables has also been confirmed in granulomas composition, The increase in the ratio of the macromolecules (collagen, glycoproteins) in both the soluble and insoluble fractions of granuloma extracts can be interpreted as a sign of the increased degradation of these tissue constituents [13].…”
Section: Introductionmentioning
confidence: 99%
“…Avocado extract stimulates stroma-related enzymes, while soybean extract alone sensitively stimulates lysosomal enzymes with an acidic pH and, to a lesser extent, some neutral lysosomal proteases [11]. Consequently, the association of both extracts which constitute ASU exerts more powerful synergistic effects, different from that exercised by each of the individual components [12]. The action of both unsaponifiables has also been confirmed in granulomas composition, The increase in the ratio of the macromolecules (collagen, glycoproteins) in both the soluble and insoluble fractions of granuloma extracts can be interpreted as a sign of the increased degradation of these tissue constituents [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, it has been indicated that ASU administration inhibits potentially inflammatory cytokines, such as TNF‐α, IL‐1, IL‐6, IL‐8, and PGE2 via modulation of NF‐kappa B in vitro and in vivo (Au et al, 2007 ; Goudarzi, Partoazar, et al, 2020 ; Taylor et al, 2017 ). ASU also has the anticonvulsant effect by enhancing GABAergic neurotransmission in the mice brain (Goudarzi, Zamanian, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arthrocen, avocado/soybean unsaponifiables (ASU), compound is an oily extract containing phytosterols, lipophilic vitamins, and terpenoids, classified as a dietary supplement in the US. Previous studies have shown that ASU compound plays a key role in the treatment of osteoarthritis (OA), reducing pain and inflammation (Goudarzi, Nasab, et al, 2020 ; Taylor et al, 2017 ), as well as reducing the expression of inflammatory cytokines and prostaglandin E2 and inhibition of COX‐2 (Au et al, 2007 ). Recent studies have also shown that ASU has anticonvulsant (Goudarzi, Zamanian, et al, 2020 ) and anti‐ischemic effects (Yaman et al, 2007 ) in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…A study designed nano‐drug delivery systems for loading avocado soy unsaponifiable (ASU), which synergistically enhanced ASU anti‐inflammatory effects with Lip 94,95 . The ASU combination inhibits nuclear factor kappa B (NF‐kB), monocyte migration as well as decreases the side effects due to the co‐delivery of ASU within Lips vesicles 96,97 . The loaded Lip with ASU has shown positive effects in controlling and reducing joint inflammation in osteoarthritis models.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%